Unemployment and the earnings structure in Latvia - Hazans, Mihails (Policy research working paper, 2005)
"Latvia has recorded sustained GDP and productivity growth since 1997. Yet unemployment rates, despite gradual decrease, have remained high. Hazans explores the mysteries of unemployment in Latvia. He analyzes labor flows between employment, unemployment, and nonparticipation and finds the following results: * The type of education and the region of residence appear to be the most important determinants of success in finding jobs by the unemployed. * The unemployed from ethnic minorities have lower chances to find a job within a year, other things equal, while the difference between genders is not significant. However, neither ethnicity nor gender seems to matter as far as the transition from employment to unemployment is concerned. * Regional disparities in job destruction seem to be less sizable than disparities in job creation. * The analysis of job search methods by the unemployed indicates that two target groups of state employment policy (young unemployed and long-term unemployed) appear to make relatively little use of the public employment service. The author also looks at the impact of education, age, gender, ethnicity, and regional factors on individual earnings. The relative position of youth and women in Latvian labor market, compared with prime?age men, is less unfavorable than in many other countries. Yet the gender wage gap has increased recently, and the same is true for regional disparities. Beneficiaries of the so-called "new" education system have a relatively high market value, especially with graduates from universities and general secondary schools. Finally, returns to experience seem to be nonexistent for many adult workers without higher education. This paper--a product of the Poverty Reduction and Economic Management Division, Europe and Central Asia Region--is part of a larger effort in the region to understand labor market dynamics"--World Bank web site